(untitled) - Stanley, George Edward; Francis, Guy (Random House, 2003)
Eight-year-old superspy Adam Sharp is summoned to cowboy-infested London to find out who stole Big Ben.
Keywords: Juvenile literature; Cowboys; Fiction; Spies; Fiction; London (England); Fiction; England; Fiction